Numerical analysis of the heat transfer and pressure drop of a wavy fin and Kammtail tube condenser: An investigative study - Sahnali, Funda Erdem; Atayilmaz, S. Ozguer; Gemici, Zafer (ELSEVIER, 2024)
The aim of this study was to numerically investigate the factors affecting the air -side performance of an innovative condenser for a domestic refrigerator. Novel condenser with a smooth Kammtail tube form was investigated due to delaying flow separation. For the first time in the literature, the kammtail form was used instead of round or ellipse geometry in a finned tube heat exchanger, and the advantages of this form was demonstrated both experimentally and numerically. This study incorporated design parameters such as air velocity (0.5, 0.7, 1 m/s), number of tube rows (4 or 5), tube arrangement (inline, staggered), fin pitches (5, 7, 10, 5-7, 5-10, 7-10 mm), and fin arrangement (homogeneous or hybrid). The findings indicated that, for identical fin types and fin surface areas, the proposed Kammtail shape of 3 x 6 mm exhibited 19% lower pressure drop and 9% higher heat -transfer coefficient compared to the original circular tube profile. Furthermore, decreasing the fin pitches resulted in a 32.9-97% increase in static pressure drop, while the heattransfer coefficient decreased by about 4.7-11.7%. The examination of two new designs revealed a marked reduction of 7-20.4% in the static pressure drop, a decline in air flow rate of 30%, an increase in heat transfer of 5.6-12.2%, and a corresponding decrease in the volume of the condenser of 20%. The numerical results of this study are in good agreement with experimental results, with deviations of less than 10%.
Keywords: Fin and tube heat exchanger; Tube shapes; Computational fluid dynamics; Experimental validation; Fin optimization; THERMAL-HYDRAULIC PERFORMANCE; AIR-SIDE PERFORMANCE; PLATE FIN; EXCHANGER; NUMBER; PARAMETERS; BANK; Thermodynamics